PSYCHOLOGICAL CHARACTERISTICS OF BULLYING IN YOUNG SCHOOL-AGE CHILDREN AND PREVENTION STRATEGIES - Gulmira Jurayevna Berdiyeva; Musayeva Munisa Suxrob qizi (The Conference Hub, 2025)
This thesis discusses the manifestation of bullying behavior, the relationship between bullying and aggressive behavior in schoolchildren, and the negative impact of bullying on students involved in such situations. The consequences of bullying and its harmful effects on students are examined, along with strategies for preventing bullying in schools.
Keywords: Bullying behavior, proactive aggression, reactive aggression, direct and indirect bullying.